Superstition in Pashto Tapa - Ahmad, Mazhar; Seemab, Sher Zaman; Mukhtiar, Paghunda (sourcecoder, 2024)
Thousands of years ago, human life was completely different. In terms of genres, Pashto literature has an easy and flowing genre through which the talk is easily understood. Pashto Tapa is the spokesperson for the environment and people’s thoughts and feelings. Pashto Tapa is the guardian of Pashtun traditions. The superstition found in the Pashtun nation is also found in the Pashto Tapa among other things. In this article, the superstition in the Pashtun nation is being brought to the fore through tippa. There are more superstitions among the Pathans compared to other nations, the main reason for this is the presence of Hindus in this region, this is the reason why there is a mention of the superstitions of the Pakhtuns in the Pashto Tapa in the literary genres, which has been included in this article.